Systematic Bibliographic Review about the Paraguay-Parana Waterway Hub (Research, Society and Development, 2022)
Physical integration through transport infrastructure can generate social and economic benefits because it optimizes the movement of goods and people. For the States Parties of MERCOSUR and IIRSA, the fluidity of transport networks is relevant, and the geographic configuration poses challenges to regional integration. The Paraguay-Paraná Waterway (HPP) would be a strategic route to be connected with other modes and become a central hub for regional development, however, it has been made impossible by political, economic, social, and environmental variables that impede physical fluvial integration. This article aims to know the art state regarding the Paraguay-Paraná Waterway. The methodology used was the Systematic Literature Review, and the chosen database was the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES). Of 93 articles identified, only 27 are included in the research scope according to the established criteria. After analyzing and cataloging the articles, it's concluded that problems are making the integration of transport infrastructure through the Platine rivers unfeasible, due to the little participation of the private sector in project financing, lack of consensus regarding environmental impact studies, and regulatory discrepancies between national and regional bodies.